Angela Vode - Mara Čepič - Kavčič, Silvija (Acta Histriae, 2007)
Angela Vode was one of the founding members of the Communist Party before the Second World War and a well-known activist of the Women's Rights Movement. She was interned in the Ravensbrück concentration camp from February to September, 1944. After returning home, the Communist Party (from which she hadbeen ousted in 1939) had come to power and she was imprisoned again. Following her release in 1953 she remained socially and politically isolated for the rest of her life. She died in 1985. Although written in 1946, her memoirs of the Ravensbrück Concentration Camp were only published in 2000. Mara Čepič was also a pre-war member of the Communist Party. She was sent to Ravensbrück as early as 1941 and remained interned there till the liberation. After the end of the Second World War she resumed her active role in politics and was also very much involved in international circles of former prisoners. The aim of my paper is to present these two personalities of Slovene history and show how and why their perspectives of the Ravensbrück Concentration Camp differed so considerably. The fact that they held two quite distinct positions in Ravensbrück and led completely different lives after the war greatly influenced their memoirs. I will support my thesis with a few quotes from their memoirs
Keywords: Čepič, Mara; druga svetovna vojna; koncentracijska taborišča; Ravensbrück; spomini; Vode, Angela, 1892-1985; World War II